The republic of skill artisan mobility, innovation, and the circulation of knowledge in premodern Europe - Garrioch, David 1955- (Brill, 2022)
"Artisans travelled all over Europe in the pre-modern period, and they were responsible for many technical innovations and new consumer products. This volume moves away from the model of knowledge 'transfer' and, drawing on new understandings of artisan work, considers the links between artisan creativity and mobility. Through case studies of different industries, it emphasizes traditions of migration, the experience of moving, and the stimulus provided by new economic and work environments. For both male and female artisans, the weight of these factors varied from one trade to another, and from place to place."
Includes bibliographical references and index
Keywords: Geschichte 1450-1800; Künstler; Kreativität; Kulturvermittlung; Kunstproduktion; Mobilität; Europa; 1580-1820; Handwerksberufe / (DE-627)091365392 / (DE-2867)18509-0; Arbeitsmigranten / (DE-627)091348838 / (DE-2867)11268-3; Innovation / (DE-627)091367840 / (DE-2867)10459-1; Qualifikation / (DE-627)091384966 / (DE-2867)19112-1; Kreativität / (DE-627)091372690 / (DE-2867)18070-3; Soziales Netzwerk / (DE-627)09139015X / (DE-2867)16595-5; Wirtschaftsgeschichte / (DE-627)091400961 / (DE-2867)15706-6; Europa / (DE-627)091358523 / (DE-2867)16815-3; Artisans / Europe / History / To 1500; Skilled labor / Europe / History / To 1500; Diffusion of innovations / History / To 1500; Labor mobility / Europe / History / To 1500; Aufsatzsammlung; Fallstudiensammlung